2020
DOI: 10.3390/atmos11020128
|View full text |Cite
|
Sign up to set email alerts
|

Radial Distributions of Sea Surface Temperature and Their Impacts on the Rapid Intensification of Typhoon Hato (2017)

Abstract: As a category-3 typhoon, Hato (2017) experienced the notable rapid intensification (RI) over the hot sea surface before its landfall. The RI process and the influences of local sea surface temperature (SST) patterns on the evolution of Hato were well captured and carefully investigated using a high-resolution air–sea coupled model. To further explore the close relationship between the radial distributions of SST and storm evolution, a sensitive experiment with time-fixed SST was also performed. Results showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…Many studies have shown high sea surface temperatures (SSTs) provide necessary energy for TCs by increasing air‐sea enthalpy (heat/moisture) fluxes, resulting in more sustained eyewall convection, warmer cores, lower central pressures, and stronger maximum winds (Emanuel et al., 2004; Jaimes et al., 2015; Zhang, Kalina, et al., 2020; Zhang, Zhang, et al., 2020). Simultaneously, however, stronger near‐surface winds impede TC intensification in two ways: frictional dissipation (Wang & Xu, 2010) and SST cooling.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown high sea surface temperatures (SSTs) provide necessary energy for TCs by increasing air‐sea enthalpy (heat/moisture) fluxes, resulting in more sustained eyewall convection, warmer cores, lower central pressures, and stronger maximum winds (Emanuel et al., 2004; Jaimes et al., 2015; Zhang, Kalina, et al., 2020; Zhang, Zhang, et al., 2020). Simultaneously, however, stronger near‐surface winds impede TC intensification in two ways: frictional dissipation (Wang & Xu, 2010) and SST cooling.…”
Section: Introductionmentioning
confidence: 99%